2019
DOI: 10.3390/jcm8111810
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Health-Related Quality of Life in Community-Dwelling Older Adults: A Multinomial Logistic Analysis

Abstract: The main aim of this study was to determine the association of various clinical, functional and pharmacological factors with the physical (PCS) and mental (MCS) summary components of the health-related quality of life (HRQoL) of community-dwelling older adults. Design: Cross-sectional study. Patients and setting: Sample of 573 persons aged over 65 years, recruited at 12 primary healthcare centres in Málaga, Spain. Sociodemographic, clinical, functional, and comprehensive drug therapy data were collected. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
1
10
1
1
Order By: Relevance
“…Concerning gender differences, our findings supported previous studies, which reported a poorer health-related quality of life among women than among men [48][49][50]. In the present study, male older adults were more often currently employed and living with a spouse than female older adults.…”
Section: Longitudinal Changes In Health-related Quality Of Lifesupporting
confidence: 91%
“…Concerning gender differences, our findings supported previous studies, which reported a poorer health-related quality of life among women than among men [48][49][50]. In the present study, male older adults were more often currently employed and living with a spouse than female older adults.…”
Section: Longitudinal Changes In Health-related Quality Of Lifesupporting
confidence: 91%
“…Similar to other studies the presence of PIMs was not correlated with poorer QoL [ 1 ]. Whilst frailty has previously been linked with poorer HRQoL (SF-12) [ 11 ], this was not replicated in our study. However, the majority of our cohort was not frail i.e.…”
Section: Discussioncontrasting
confidence: 86%
“…Our study results are in accordance with the studies performed by Primejdie et al in 2012 and, which highlighted that NSAIDs, benzodiazepines, zopiclone, and zolpidem are the pharmaceutical substances most frequently associated with safety concerns in ambulatory as well as in institutionalized patients [21,22]. In a study performed in Spain in 2019, where the two versions of the Beers criteria (2012 and 2015) and the two versions of the STOPP criteria (v.1, 2008 and v.2, 2015) were applied, benzodiazepines, proton-pump inhibitors, peripheral alpha-1 blockers, and NSAIDs were among the most common potentially inappropriate medications found [64]. Another study performed in Brazil in very old hospitalized patients emphasized (after applying the 2019 Beers criteria) that polypharmacy occurs in approximately 84.6% of cases and that the most commonly encountered PIMs are metoclopramide, omeprazole, regular insulin, and haloperidol [65].…”
Section: Correlations With the Scientific Literaturementioning
confidence: 99%